Interaksi Genotipe – Lingkungan Galur Harapan Padi Rawa - M. Sabran; S. Sulaiman; I. Khairullah; M. Imberan; M. Saleh (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
A study was conducted in 7 location represent to sulfuric-acid, peat or arable land in order to define productivity of several promoting lines of swamp-rice. Foerteen lines with two control varieties were tested in each location. The lines were grown in two different NPK-fertilization, i.e. low and high dosage of NPK. Yhe study was objected to define the genotype-environment or non-specific environment. The result show that the tested-lines adapted to the specific environment, but not to non-specific environment.